(untitled) (NTU Journal of Engineering and Technology, 2026)
The main environmental impact of concrete comes from raw mill dust and carbon dioxide emissions during cement production. This paper reviews the effect of raw mill dust on the mechanical properties of concrete, the development and improvement of concrete mixtures, and the use of raw mill dust as a partial cement substitute to eliminate the environmental impact of raw mill dust. This dust is used to reduce energy consumption and carbon dioxide emissions. This is achieved by replacing cement with raw mill dust used in the cement industry. To study the effect of using raw mill dust as a partial cement substitute in concrete, special attention was paid to the physical and chemical properties of the material. This paper aims to evaluate the potential of using this dust, a by-product of the cement industry, to improve concrete performance while reducing environmental impacts. It also evaluates the effect of different proportions of mill dust as a partial cement substitute on compressive strength, tensile strength, and workability. The results showed that incorporating mill dust in specific proportions improved some mechanical properties, such as increased long-term compressive strength, while slightly reducing tensile strength compared to conventional concrete. The addition also contributed to improving the sustainability of concrete by reducing cement consumption and carbon dioxide emissions.